The subjective well-being of workfare participants: Insights from a Day Reconstruction Survey - Ronnie Schöb; Andreas Knabe; Joachim Weimann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we shed more light on the subjective well-being of workfare participants and compare it to the well-being of unemployed and employed workers. We use data from a self-conducted survey among participants in workfare schemes in Germany. We examine two subdimensions of subjective well-being – life satisfaction and emotional well-being – separately to obtain a more comprehensive view of the subjective well-being of workfare participants. Our results show that the life satisfaction of people in this group is between that of employed and unemployed people. In contrast, their emotional well-being is the highest of these three groups.
Keywords: I31; J60; D60; 330